Perception of patients with type 2 diabetic mellitus towards insulin therapy - Rose A Nain; Rosalin Sulit (Malaysian Journal of Medicine and Health Sciences, 2020)
Insulin therapy is one of the prominent treatment methods to regulate the glucose level in blood. However, there are certain patients who refuse to even begin the insulin therapy. It is importance to identify patients’ perception and their acceptance of insulin therapy. Purpose of this study is to determine the perception of patients with Type 2 diabetes mellitus towards insulin therapy. and to identify the differences in perception based on the respondents’ age, gender, occupations and educational level. Methods: This is a quantitative descriptive study and was done in one of diabetic clinic in Kota Kinabalu, involving 50 patients with Type 2 Diabetes Mellitus and was not on insulin therapy. Participants were recruited via purposive convenience sampling. Questionnaires were used as research instrument. Results: Majority of the participants (80%) have negative perceptions towards insulin therapy and 84% refused insulin therapy because it would interfere with their working time and routine. Acceptance of insulin therapy among the female patients (Mean = 3.0) was better than the male patients (Mean = 2.8). Patients with high educational level were more positive in accepting insulin therapy (SM > 0.5). Age and occupation factor were categorized as the strong influential factors (SM < 0.5) in determining the patients’ perception towards insulin therapy. The significant mean (mean ± SD) for gender and educational factor showed more than 0.5 hence suggests positive perception in accepting insulin therapy. While, the significant mean (mean ± SD) for age and occupation factor showed less than 0.5 thus suggests negative perception in accepting insulin therapy. Conclusion: Participants have negative perceptions towards insulin therapy and these negative perceptions may possibly deter them from receiving insulin therapy. Appropriate health education and counselling is necessary to help them change their negative perceptions.